The Use of Associations Between Anthropometric and Food Variables in the Assessment of Nutritional Status of Queens College Students of Lagos State, Nigeria - Akinyemi, O. (Pakistan Journal of Nutrition, 2009)
Traditionally, malnutrition is identified using anthropometric indices based on NCHS/WHO reference standards, in this paper, we explore the associations that exist between anthropometric and nutrition variables for assessing the nutritional status of Queens College Students of Lagos State, Nigeria. Results show that the nature of associations are causally related to nutritional status; the participants are not adequately fed on protein which might be a contributing factor to students’ poor performance in the boarding secondary school. Tests on correlation and regression show that food intakes are not associated with physical characteristics but with food intakes. The implications of the findings are discussed and suggestions on ways to alleviate the problems.